Investigation of the Sympathetic Regulation in Delayed Onset Muscle Soreness: Results of an RCT - Fleckenstein, Johannes; Neuberger, Elmo W. I.; Bormuth, Philipp; Comes, Fabio; Schneider, Angelika; Banzer, Winfried; Fischer, Lorenz; Simon, Perikles (Frontiers in Physiology, 2021)
Sports-related pain and injury is directly linked to tissue inflammation thus involving the autonomic nervous system (ANS). In the present experimental study, we disable the sympathetic part of the ANS applying a stellate ganglion block (SGB) in an experimental model of delayed onset muscle soreness (DOMS) of the biceps muscle. We included 45 healthy participants (female 11, male 34, age 24.16 ± 6.67 years [range 18-53], BMI 23.22 ± 2.09 kg/m2) which were equally randomised to receive i) a SGB prior to exercise induced DOMS (preventive), ii) sham intervention in addition to DOMS (control/sham), or iii) SGB after the induction of DOMS (rehabilitative). Aim of the study was to determine whether and to what extent sympathetically maintained pain (SMP) is involved in DOMS processing. Focusing on the muscular area with the greatest eccentric load (biceps distal fifth), a significant time x group interaction on the pressure pain threshold was observed between preventive SGB and sham (p = 0.034). There was a significant effect on pain at motion (p = 0.048), with post-hoc statistical difference at 48 hours (preventive SGB Δ1.09 ± 0.82 cmVAS vs. sham Δ2.05 ± 1.51 cmVAS; p = 0.04). DOMS mediated an increase in venous cfDNA -as a potential molecular/inflammatory marker of DOMS- within the first 24 hours after eccentric exercise (time effect p = 0.018), with a peak at 20 and 60 minutes. After 60 minutes, cfDNA levels were significantly decreased comparing preventive SGB to sham (unpaired t-test p = 0.008). At both times, 20 and 60 minutes, cfDNA significantly correlated with observed changes in PPT. The 20-minutes increase was more sensitive, as it tended towards significance at 48 hours (r = 0.44; p = 0.1) and predicted the early decrease of PPT following preventive stellate blocks at 24 hours (r = 0.53; p = 0.04) Our study reveals the broad impact of the ANS on DOMS and exercise-induced pain. For the first time, we get insights in the sympathetic regulation of pain and inflammation following exercise overload. As this study is of translational pilot character, further research is encouraged to confirm and specify our observations.